Primary Prostate Lymphoma Managed with Combined Modality Treatment: A Case Report - Jafari, Anya; Mofid, Bahram; Tabibi, Ali; Kowsari, Farid (Urology Journal, 2019)
Prostate cancer is one of the most common malignancies in men; the main reported pathology is adenocarcinoma while there are few published cases of prostate lymphoma. There isn’t enough data regarding the natural history and best management of prostate lymphoma. In this paper, we have described a case of prostate lymphoma that managed with combined modality treatment and have been survived for three years.